2013
DOI: 10.3141/2344-11
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Use Development Trip Generation Model

Abstract: The mixed-use development (MXD) trip generation model provides a mechanism for estimating vehicle, walking, and transit trips for an MXD. The model applies trip modifications to standard single-use trip generation estimates developed by ITE. MXDs with diverse internal activities have been shown to capture internal trips at a rate higher than conventional suburban developments; therefore, the MXD trip generation model accounts for the internal capture of MXD sites by reducing the external trips produced and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In contrast, the ITE manual does not provide data for individual sites, and although some filtering is possible based on location type, geographical region, and development size, no other contextual information is available. As a result, much research has been undertaken in the United States to develop methods that can adjust ITE vehicle trip generation rates to better reflect the local site context, generally based on vehicle mode share and occupancy rate information ( 3 , 8 , 13 , 25 , 86 , 90 , 109 , 110 , 121 , 122 ). These adjustments are particularly relevant for highly urbanized areas with low car use, as the ITE rates are almost all based on trip generation studies undertaken in low-density suburban areas with relatively high levels of car use ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the ITE manual does not provide data for individual sites, and although some filtering is possible based on location type, geographical region, and development size, no other contextual information is available. As a result, much research has been undertaken in the United States to develop methods that can adjust ITE vehicle trip generation rates to better reflect the local site context, generally based on vehicle mode share and occupancy rate information ( 3 , 8 , 13 , 25 , 86 , 90 , 109 , 110 , 121 , 122 ). These adjustments are particularly relevant for highly urbanized areas with low car use, as the ITE rates are almost all based on trip generation studies undertaken in low-density suburban areas with relatively high levels of car use ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many scenario planning tools rely on research from Ewing and Cervero (2010), and on the work behind other tools, such as the MXD tool developed by Ewing et al (2013), which relies on such measures as intersection density and a measure of entropy for mixed-land uses, which are really too coarse to truly understand what happens when new facilities are put in 13 Background and Overview of Planning Support Tools (PSTs) for bicycling, pedestrians, or emerging services, such as e-scooters and NEVs. Promising research to address these issues can be found in LA Metro's bike modeling project and research currently underway at SDSU's Active Transportation Research Center.…”
Section: Section Conclusionmentioning
confidence: 99%
“…This is critical, as many of even our best scenario planning models and tools do not do much in the way of appreciating new facilities for bicycles, pedestrians, or even such new modes as neighborhood electric vehicles. The MXD model developed by Ewing et al (2013), for example, is limited to measuring intersection density, which-while effective-is a rather coarse measure of pedestrian/bicycle facilitation (Ewing et al, 2011).…”
Section: Context (Place Type)mentioning
confidence: 99%
“…The economically active percentage of the population is considered to calculate the home based work trips and to calculate the number of motorized trips, the vehicle registration percentage is considered in the study area. (Gulden, Goates, & Ewing, 2013)…”
Section: Calculation Of Total Trip Generation and Attractionmentioning
confidence: 99%